Students’ Perception on The Implementation of Orai Application In CLL Method in Teaching Speaking - Halimah; Lustyantie, Ninuk; Ibrahim, Gufran Ali (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2018)
This study aims to examine EFL learners’ perception toward the application of Orai App in CLL method in teaching speaking. The study employed likert-scale questionnaires to enable researchers to collect massive data. The total of 24 first year students of a private university in East Java – Indonesia, comprising of 5 male and 19 female students participated in this study. Data were analyzed using descriptive statistic by finding out the total score per item. The results of this study illustrated that Orai application helps students alleviate the fear of speaking. It can also help students in increasing their speaking ability on the aspects of pronunciation, intonation as well as the speaking speed. Based on the data analysis, CLL method assisted by Orai application is strongly recommended to be used to assist the students to be better speaker.